PROXIMATE COMPOSITION OF EDIBLE SHELLFISHES FROM BUGUMA CREEK, RIVERS STATE, NIGERIA. - DAVIES, I. C.; HART, A. I; JAMABO, N. A (Nigerian Journal of Fisheries, 2017)
This study was conducted in order to determine the proximate composition of selected shellfishes from the Buguma creek in Rivers State, Nigeria. The edible parts of shell fishes (Tympanotonus fuscatus, Thais coronata, Callinectes amnicola, Cardisoma guanhumi, and Crassostrea gasar) were analysed for their proximate composition (ash, fat, moisture and protein content). T. fuscatus had the lowest moisture content (32.6 + 0.05%) and the highest crude protein level (64.2 + 0.04%). The results of the study showed that the shellfishes contain low fat (9.59 +0.27), carbohydrates (0.75 + 0.21%) and ash (9.59 + 0.27%) and therefore will not enhance obesity. These values are useful references for consumers in order to choose shellfish based on their nutritional contents.